Accelerated Life Testing of Electronic Devices by Atmospheric Particles: Why and How - Frankenthal, R. P.; Siconolfi, D. J.; Sinclair, J. D. (Journal of the Electrochemical Society, 1993)
Airborne particles can severely degrade electronic equipment and systems by adhering to surfaces and then adsorbing moisture on the particle surface, which in turn captures corrosive gas molecules that form corrosive solutions that then attacks structures (wires, insulation, components, etc.). An accelerated life testing chamber subjects equipment to dust and ions at various velocity and humidity conditions. 32 refs.